A Pyrazole‐Based Highly Selective Colorimetric Chemosensor for Hg2+ Ion in Semi‐Aqueous Medium. Issue 1 (2nd January 2020) - Karuppusamy, P.; Senthilvelan, J.; Vijayakumar, V.; Sarveswari, S.
Abstract: In this study, a pyrazole‐based (Py‐KS) chemosensor was successfully designed and synthesized via Knoevenagel condensation and utilized as a colorimetric chemosensor for selective determination of Hg 2+ in semi‐aqueous media. The probe exhibits a typical absorption band at 519 nm upon interaction with Hg 2+, which is responsible for remarkable color change from yellow to pink. The detection limit of Py‐KS for the analysis of Hg 2+ was found to be 4.73×10 −7  M. The binding modes of interaction of Py‐KS with Hg 2+ have been determined by Job's plot which exhibits 2:1 (Py‐KS: Hg 2+ ) ratio, and further confirmed with 1 H NMR titration and FT‐IR analysis. The association constant of Py‐KS ‐Hg 2+ complex was found as 1.2×10 3  M −1 using Benesi‐Hildebrand method. The probe could be recyclable after appropriate treatment with the reagents such as EDTA. Moreover, the designed probe Py‐KS has successfully demonstrated for the detection of Hg 2+ in real sample analysis. Abstract : Pyrazole based chemosensor with good selectivity towards Hg 2+ ion is reported. The stoichiometric complexation ratio was found to be a 2:1 (L: M) ratio of probe Py‐KS and Hg 2+ . The limit of detection was calculated for Hg 2+ is 4.73×10 −7  M. The probe Py‐KS can serve as Hg 2+ ion sensor without using any sophisticated or complicated instruments. The probe Py‐KS effectively utilized for environmental applications.